The Fan-Raspaud conjecture: a randomized algorithmic approach and application to the pair assignment problem in cubic networks - Formanowicz, Piotr; Tanaś, Krzysztof (Zielona Góra: Uniwersytet Zielonogórski)
It was conjectured by Fan and Raspaud (1994) that every bridgeless cubic graph contains three perfect matchings such that every edge belongs to at most two of them. We show a randomized algorithmic way of finding Fan-Raspaud colorings of a given cubic graph and, analyzing the computer results, we try to find and describe the Fan-Raspaud colorings for some selected classes of cubic graphs
Keywords: cubic graph; edge coloring; perfect matching; randomized algorithms; computer networks